Congenital Chloride Diarrhoea In Relation With Renal Complications (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the significance of early detection of renal complications in children with congenital chloride diarrhoea.Study Design: Retrospective study.Place and Duration of Study: This study was done for the time period from March, 2003- September, 2016 in the department of Paediatric Gastroenterology, Hepatology & Nutrition, KFSH&RC, Jeddah.Materials & Methods: This retrospective study was carried out for the time period starting from March, 2003- September, 2016 for 19 confirmed cases of congenital chloride diarrhoea at KFSH&RC, Jeddah.Results: Out of19 cases we found 13(68.4%) patients with renal abnormalities. We found 2 cases (15.3%) with end stage renal disease, 3 cases (23%) of nephrocalcinosis, 7 cases (53.8%) with increased echogenicity of both kidneys and 1 case (7.6%) of renal stones.Conclusion: We conclude that by increasing the level of understanding of disease and keeping good compliance with daily medications, the renal complications could be prevented to improve the outcome.
Keywords: Congenital chloride diarrhoea (CLD), renal complications, compliance, outcome.